PERAN PEREMPUAN DALAM MENGURANGI KEMISKINAN - Aprillia Elly Kusumastuti (ECONBANK: Journal of Economics and Banking, 2019)
This study aims to analyze the phenomenon of the emancipation of women's roles, credit and poverty. A total of 100 members of the women's savings and loan group and recipients of economic aid funds were taken as samples with purposive sampling. Multiple linear regression analysis has been used to analyze the data in this study. The results showed that the Productive Economic Business loans have not effect to reduce Poverty, while loans from the Women's Savings and Loans group have effect to reduce Poverty. Incomplete information is the cause of not yet optimal loans. Therefore, the community must continue to do business management training to obtain loans that can be managed properly which will improve the progress of the business being carried out. In addition, it is necessary for women or mothers to need information about women's savings and loans activities intended for those who need business capital not for consumptive activities.